The Influence Of Communication Ethics, Information Systems, And Work Environment On Employee Performance At Bank Central Asia KCP HM Yamin Medan - Sarah Isabella Sihombing; Yohny Anwar; Wilchan Robain (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to determine the effect of communication ethics, information systems, and work environment on employee performance at PT. Bank Central Asia, Tbk KCP HM Yamin Medan. The object of this study was all employees working at Bank BCA KCP HM Yamin Medan with a sample of 47 people. The data analysis technique used multiple linear regression analysis. The partial results of the study showed that communication ethics had a significant effect on employee performance with a t-count value of 3.139> 1.681 and a significance value of 0.003 <0.05 then the information system variable had a significant effect on employee performance with a t-count value of 2.125> 1.681 and a significance value of 0.001 <0.05 then the work environment variable had a significant effect on employee performance with a t-count value of 3.139> 1.681 and a significance value of 0.039 <0.05. Furthermore, it simultaneously shows that communication ethics, information systems, and work environment have a significant effect on employee performance with an F-count value of 17,494 > 2,820 and a significance value of 0.001 < 0.05. In addition, 74.8% of employee performance variables are influenced by communication ethics, information systems, and work environment, while the other 25.2% are other variables outside the study.